How to change or transform a coordinate system into a map layer? The answer is in ArcMap - Grifo, Anabela (2014)
The application of new technologies to agricultural activity, associated with the Global Positioning System, generates high amount of georeferenced information. Thus, we are often confronted with different assignments of coordinate systems. The transformation of data from one source of information into the data coordinate system from another source is a prior and fundamental step to any analysis of georeferenced information. This study aims to know and understand the transformation process of geographical coordinates into rectangular ones and vice versa, as well as the transformation between different coordinate systems, through the ArcMap software tools because it is a question often asked by students and others who try to use the Geographic Information Systems tools.----A aplicação das novas tecnologias à atividade agrícola, associada aos Sistemas de Posicionamento Global, gera elevada quantidade de informação georreferenciada. Deste modo, somos muitas vezes confrontados com atribuições distintas de sistemas de coordenadas. A transformação dos dados provenientes de uma das fontes de informação no sistema de coordenadas dos dados provenientes de outra fonte é uma etapa prévia e fundamental para qualquer análise de informação georreferenciada. Este trabalho tem como objetivo conhecer e entender o processo de transformação de coordenadas geográficas em retangulares e vice-versa, bem como a transformação entre sistemas de coordenadas distintos, através das ferramentas do software ArcMap por ser uma questão colocada frequentemente por alunos e outros utilizadores que tentam utilizar as ferramentas Sistemas de Informação Geográfica.